2018
DOI: 10.12928/telkomnika.v16i0.7722
|View full text |Cite
|
Sign up to set email alerts
|

Lowpass Filter with Hilbert Curve Ring and Sierpinski Carpet DGS

Abstract: Good performance and compact size are the paramaters which are vital when desiging a filter. One of the creteria of good performance is selectivity. This research, conducted by Hilbert Curve Ring and Siepinski Carpet, is used as defected ground structure to overcome filter selectivity. By using three cascadeds Hilbert Curve Ring defected ground structure cells and three steps Sierpinski carpet, a lowpass filter is designed and fabricated. The measurement result for lowpass filterwith Hilbert Curve Ring defecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This method is called a Defected Ground Structure (DGS). DGS is a microstrip antenna technique by defecting some structure on the ground surface of microstrip planar for enhancing gain and bandwidth purposes [18] [19]. Slotting size is represented by GW and GL , which are 33 mm and 45.5 mm, respectively [20].…”
Section: Defected Ground Structure (Dgs) Designmentioning
confidence: 99%
“…This method is called a Defected Ground Structure (DGS). DGS is a microstrip antenna technique by defecting some structure on the ground surface of microstrip planar for enhancing gain and bandwidth purposes [18] [19]. Slotting size is represented by GW and GL , which are 33 mm and 45.5 mm, respectively [20].…”
Section: Defected Ground Structure (Dgs) Designmentioning
confidence: 99%
“…The need for an effective separation of signals with different frequencies reflects in many researches of highly selective bandpass and lowpass filters [1][2][3][4][5]. In [1], a bandpass filter with four open loop rectangular resonators was implemented in lossy substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the bandwidth increased and a pair of transmission zeros were generated due to suitable dimension of the resonators. In [5], compact sized lowpass filters with good performance in selectivity were introduced. The work was based on modification of the ground of a simple microstrip line.…”
Section: Introductionmentioning
confidence: 99%